Effect of Arrabidaea Chica Verlot Hydroalcoholic Extract on Monosodium Iodoacetate-Induced Osteoarthritis of Rat Knees / Efeito do Extrato Hidroalcoólico de Arrabidaea chica Verlot na osteoartrite induzida por Monoiodoacetato de Sódio em joelhos de ratos - Servin, Elizabeth Teixeira Noguera (2020)
Introdution: The Arrabidaea chica Verlot (A. chica, ACV), with well-demonstrated anti-inflammatory properties,  appears as an option with therapeutic potential for the osteoarthritis; thus, validating its use is highly relevant. Method: 72 rats were allocated to 3 groups: control, osteoarthritis and phytotherapy {these last two were subjected to osteoarthritis induction, and treated orally with 0.9% normal saline (0.1 mL/100 g) and ACV hydroalcoholic extract (500 mg/kg), respectively, from days 7 to 28}. The 3 groups were subjected to weekly (days 7, 14, 21, 28) assessments including clinical tests (weight-bearing and von Frey), radiological and histopathological analyses.  Fractionation of the ACV´s hydroalcoholic extract was performed and it´s fractions were analysed. Results: The evaluation of the values of the osteoarthritis and phytotherapy groups showed significant difference, with p <0,05 : weight-bearing- on days 14 (29,64 x 35,52), 21 (32,62 x 42,53) and 28 (33,56 x 47,14), von Frey- on days 14 (31,12 x 37,80), 21 (30,24 x 41,48) and 28 (35,78 x 46,09),  x-ray- on days 21 (2,17 x 1,20) and 28 (2,33 x 1,40), and histopathological analysis- on day 28 (0,03 x 2,20). The fractionation of the extract obtained the FH (hexane), FC (chloroform), FAE (ethyl acetate) and FB (butanolic) fractions. The FAE had highest total polypnenolic contents and the FH had the highest concentration of total flavonoids. Conclusion: The ACV extract promoted a reduction in static incapacitance, allodynia, radiological score and degree of synovitis, and FAE and FH fractions are probably the fractions responsible for the anti-inflammatory and analgesic activities of the ACV extract.